AWS Fargate for Flask Microservice in One Hour Video Course - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Learn to use containers to build Microservices on the AWS platform. In this video you walk through building a Flask Microservice using the following AWS tools: * AWS Cloud9 * AWS ECR (Elastic Container Registery) * AWS ECS (AWS Container Service) * AWS Fargate (Container as a Service) Finally, the course builds and deploys a Fargate container that was provisioned to ECR. Follow along with the Github Resource: https://github.com/noahgift/eks-fargate-tutorial.